Pollutants May Have Caused Morphological Abnormalities in Some Polychaete Species (Annelida) Collected from Cilacap, Central Java, Indonesia - Joko Pamungkas; Atang; Eko S. Wibowo; Misika Alam; Sri Lestari (Tropical Life Sciences Research, 2025)
Morphological abnormalities in Perinereis aibuhitensis (Grube 1878) (Nereididae) and Diopatra claparedii Grube 1878 (Onuphidae) were observed in the specimens collected from the intertidal habitat around Donan Creek in Cilacap City, Central Java Province, Indonesia. The P. aibuhitensis, which is not supposed to have branchiae, possesses digitate branchiae on its dorsum, and lacks eyes. To our knowledge, the presence of branchiae in the genus Perinereis and the shape of the feature has never been reported anywhere else. Furthermore, the D. claparedii, which is supposed to have the most developed branchiae on its dorsal anterior region, lacks the feature. The species also lacks both prostomial and peristomial appendages, and has various anomalous cirri. While the abnormalities in the P. aibuhitensis are likely to be associated with the hypoxic condition of the animal’s habitat, the anomalies in the D. claparedii appear to be more related to the exposure to pollutants, particularly heavy metals. Taxonomic investigations are required to reveal the polychaete species richness in this area, and may identify species that have the potential to be used as biological indicators of coastal water pollution in southern Java.